Uji Empirik Metode Pengukuran Hedging Ratio dan Efektivitas Hedging di Bursa Komoditas Berjangka Jakarta - Buddi Wibowo (School of Business, Bogor Agricultural University (SB-IPB), 2017)
Hedging strategies in the commodity futures market is strongly influenced by the estimation method of hedge ratio. This study examines the effectiveness of hedging strategy against cash position in Indonesia’s palm oil spot market using three hedge ratio estimation methods: OLS, Vector Error Correction Model, and Threshold-ARCH. The results show the hedging effectiveness in the Jakarta Futures Exchange is considerably highly effective to reduce the impact of fluctuations of spot price. The effectiveness of hedging strategy using OLS as the simplest method is close to VECM method and TARCH. The effectiveness of hedging strategy using OLS hedge ratio provides an opportunity for market player in implementing hedging strategy in Jakarta Futures Exchange due to its simplicity in estimation procedureKeywords: hedge ratio, hedging effectiveness, OLS, VECM, TARCH